PENGARUH LOKASI, SARANA DAN PRASARANA SERTA PELAYANAN TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA PADA LOYALITAS PELANGGAN (Studi Kasus pada hotel-hotel di Kabupaten Semarang ) - Hendrajaya, Hendrajaya (JURNAL ILMIAH EDUNOMIKA, 2023)
The aim of this research is to know the influence of the Location, Facilities and Service toward the Satisfaction of the customers and the implication toward the Loyality of customers.This research used primary data about the standart quality of location (7 items), standart quality of facilities (18 items), standart of service (16 items), standart quality of customer satisfaction (7 items) and variable of customer loyality (6 items). All items above are measured using likers scale and analized of its validity and reliability. Data gathering is using questioneair techningue to the 168 quests of hotel in Semarang. Data analysis is using path analysis, t-test, f-test and coefficient of determanition. The result of the researct shows that of the hypothesis are not all acceptable, it is incated that location doesn’t influent positively and significantly toward the customers satisfaction, mean while facilities influents positively and significantly with analysis t-test (2,160) > t-table (1,654) and analysis sig.(0,032) < (0,05), sercice influences positively and significantly toward customers satisfaction with the analysis t-test (2,411) > t-table (1,654) and analysis sig.(0,017) < (0,05), customer satisfaction is not intervening between location and customer loyality because the direct influence > the indirect influence (6,8%) > (1,6%). Customers satisfaction is entervening between facilities and customers loyality, the influence as much as (6,2 %), customer satisfaction is not intervening between service and loyality because direct influence > indirect influence (23,5%) > (6,8%), customers satisfaction influents positively and significantly toward customers loyality with the analysis t-test (11,264) >f-table (2,26) and analysis sig (0,000) < (0,05), r2 (0.199) which means it has a 19,9% positive influence toward customers loyality. Customer satisfaction is intervening between facilities toward customers loyality Hotel in Semarang. KeyWords : Location, Facilities, Service, Customers Satisfaction, Customers Loyality.